Description of Ptilohyale corinne sp. nov. (Amphipoda: Hyalidae) from the Bahía Blanca estuary, Argentina, including a key to all valid Ptilohyale species - Di Rossi, Catalina; Sciberras, Michel; Bulnes, Veronica N. (Zootaxa, 2020)
A new species of amphipod, Ptilohyale corinne sp. nov. (Hyalidae) is described from the Bahía Blanca estuary (38°53’S, 62°07’W) in Buenos Aires Province, Argentina. Ptilohyale corinne sp. nov. can be differentiated from its valid congeners by having two posterior marginal cusps on coxa 2 and 3, and asymmetrical telson lobes with a particular combination of setae: each lobe with three dorsal plumose setae and one seta on inner margin. This is the first record of Ptilohyale in South America. Additionally a key to the valid species of the genus is provided